Diagnostic performance of GeneXpert MTB/RIF assay compared to conventional Mycobacterium tuberculosis culture for diagnosis of pulmonary and extrapulmonary tuberculosis, Nepal - Raina Chaudhary; Sabita Bhatta; Alina Singh; Manoj Pradhan; Brijendra Shrivastava; Yengkokpam I. Singh; Ranjit Sah; Zareena Fathah; Rachana Mehta; Ali A. Rabaan; Alfonso J. Rodriguez-Morales; Kuldeep Dhama (Narra Sains Indonesia, 2021)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis. It is a global health problem and major cause of death in resource-limited countries like Nepal. Timely diagnosis with sensitive testing methods could assist in early management of the disease. This study was conducted to compare the diagnostic performance of GeneXpert MTB/RIF and conventional acid-fast staining with M. tuberculosis culture. The study was carried out in the Department of Microbiology, Shree Birendra Army Hospital, Nepal. Samples (n=500) were tested with a GeneXpert MTB/RIF assay and acid-fast bacilli (AFB) smear microscopy. All samples were sent for M. tuberculosis conventional culture by the German-Nepal Tuberculosis Project, Kathmandu, Nepal (GENETUP). Out of a total 500 pulmonary and extrapulmonary samples tested, 97 samples were positive for M. tuberculosis by GeneXpert MTB/RIF assay. Out of the positive samples, only 95 samples were found positive by the culture method. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of AFB microscopy was 45.3%, 99.5%, 99.5% and 88.5%, respectively. The sensitivity, specificity, PPV and NPV of GeneXpert MTB/RIF was found to be 100%, 99.5%, 97.5% and 100%, respectively compared to the gold standard culture method. The GeneXpert MTB/RIF test was comparable with culture diagnosis of both pulmonary and extrapulmonary tuberculosis cases.